2020
DOI: 10.1039/d0sm01312a
|View full text |Cite
|
Sign up to set email alerts
|

Poroelasticity of highly confined hydrogel films measured with a surface forces apparatus

Abstract: The influence of poroelasticity on the contact mechanics of thin polyacrylamide films was investigated with a surface forces apparatus (SFA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Previous studies have demonstrated that the strength of cation- interactions is highly dependent on the distance between the cationic and aromatic components, and are effective only when these two are in close proximity. 24,26 However, similar to most reported hydrogels, [44][45][46][47][48][49][50][51] the reported hydrogels with cation- interactions are highly swollen polymeric networks. [40][41][42] In these cases, the distance between the incorporated cationic and aromatic groups are dramatically increased, which greatly weaken cation- interactions in hydrogels and thus unable their self-healing performance.…”
supporting
confidence: 77%
“…Previous studies have demonstrated that the strength of cation- interactions is highly dependent on the distance between the cationic and aromatic components, and are effective only when these two are in close proximity. 24,26 However, similar to most reported hydrogels, [44][45][46][47][48][49][50][51] the reported hydrogels with cation- interactions are highly swollen polymeric networks. [40][41][42] In these cases, the distance between the incorporated cationic and aromatic groups are dramatically increased, which greatly weaken cation- interactions in hydrogels and thus unable their self-healing performance.…”
supporting
confidence: 77%
“…Further, for poroelastic materials, we expect a stiffer network transmits greater stress through the material, driving faster fluid flows as compared to a soft network. Faster fluid flow has been associated with stiffer networks previously [34][35] . In addition, the network motion captured in the imaging device demonstrates that hydrogels undergo internal lateral shearing in response to compression and a subsequent relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…For these conditions, the multi-spring model, the Winkler model, can be used. Other studies have used it to approximate the compression forces of hydrogels [58] and protein films. [59] The springs have a specified compression range, corresponding to the indentation.…”
Section: Discussionmentioning
confidence: 99%